How We Built a Virtual Scheduling Assistant at Microsoft - Monroy-Hernandez, Andres; Cranshaw, Justin (Harvard Business Review, 2017)
Many people would agree that scheduling meetings is tedious. Perhaps you have experienced an email chain like this: Jenn, a potential client: Hey! What day/time works for a quick call next week? You: (toggling between calendar app and email) I’m wide open Monday. Jenn: (several hours later) Sorry. Traveling that day. How about Wednesday at 10 AM? You: (checking your calendar app again) That should work. Your office? Jenn: My office is great. Maybe we should see if Emad can join? This back-and-forth can carry on, and it can get even more challenging when people use different calendaring systems or meet across different time zones. Not only are these exchanges time-consuming, they also obliterate our ability to focus on more demanding tasks.